Crimean-Congo hemorrhagic fever: A global perspective - (:unkn) unknown (Springer Netherlands, 2007)
Crimean-Congo hemorrhagic fever (CCHF) is a tick-borne disease associated with severe hemorrhagic manifestations. CCHF has been referred to as the Asian Ebola. However, in fact, the disease is one of the most widely distributed tick-borne diseases in the world, occurring in Africa, Asia, Europe, and the Middle East. This volume covers major aspects of this important disease and the virus which causes it. Chapters are written by leading experts in their fields and detail historical, public health, epidemiological, and clinical aspects of CCHF and the genetics and molecular biology of the virus. Additional chapters focus on disease control, tick vectors and infection among animals, both natural and experimental. This book will be of interest to virologists, microbiologists, medical entomologists, infectious disease physicians, epidemiologists, public health specialists, veterinary scientists, public health policy makers, journalists, and medical educators. © 2007 Springer Netherlands. All rights reserved.